2017
DOI: 10.5194/amt-10-2239-2017
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of radar reflectivity factor simulations of ice crystal populations from in situ observations for the retrieval of condensed water content in tropical mesoscale convective systems

Abstract: Abstract. This study presents the evaluation of a technique to estimate cloud condensed water content (CWC) in tropical convection from airborne cloud radar reflectivity factors at 94 GHz and in situ measurements of particle size distributions (PSDs) and aspect ratios of ice crystal populations. The approach is to calculate from each 5 s mean PSD and flight-level reflectivity the variability of all possible solutions of m(D) relationships fulfilling the condition that the simulated radar reflectivity factor (T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
15
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 32 publications
4
15
2
Order By: Relevance
“…Assuming that largest hydrometeors (max(D max )) can be considered a proxy for the aggregation process efficiency, the findings of this study reveal that aggregation process efficiency is higher for MCS over land than over islands and higher over islands close to large land masses than over islands in the middle of an ocean. It seems to confirm the results of Frey et al (2011) and Cetrone and Houze (2009).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Assuming that largest hydrometeors (max(D max )) can be considered a proxy for the aggregation process efficiency, the findings of this study reveal that aggregation process efficiency is higher for MCS over land than over islands and higher over islands close to large land masses than over islands in the middle of an ocean. It seems to confirm the results of Frey et al (2011) and Cetrone and Houze (2009).…”
Section: Discussionsupporting
confidence: 86%
“…MCS over Niamey also show larger max(D max ) in MCS reflectivity zones 2 to 4, illustrating that snow aggregates can reach larger sizes during the West African Monsoon than in other MCS locations. This confirms the conclusions of Frey et al (2011) and Cetrone and Houze (2009), who suggested that there are larger ice hydrometeors in MCS over continental regions than MCS over maritime regions.…”
Section: The Largest Ice Hydrometeorssupporting
confidence: 91%
“…Several numerical simulation studies on tropical MCSs sampled during the HAIC-HIWC projects have been conducted using different numerical models and different microphysics schemes. Franklin et al (2016) showed that the Met Office Unified Model (UM) with a single-moment microphysics scheme overestimated the radar reflectivity above the freezing level due to the errors of simulated updraft dynamics and particle sizes, hypothesizing that a double-moment microphysics scheme would improve the model's representation of the observed variability of the ice particle size distribution (PSD). The Stanford et al (2017) WRF simulations of four tropical deep convection events sampled during the HAIC-HIWC Darwin campaign showed that three microphysics schemes (one bin and two double-moment bulk schemes; Lynn et al, 2005;Thompson et al, 2008;Morrison et al, 2009) produced larger MMDs for TWC > 1 g m −3 at temperatures between −10 and −40 • C and a high bias in convective radar reflectivity compared to observations.…”
mentioning
confidence: 99%
“…Retrievals of ice cloud properties, such as radar reflectivity factor (Z) [1], snow rate [2,3], ice water content (IWC) [3,4] and effective density (ρ e ) [5,6] require estimates of how ice particle mass (m) varies with ice particle dimension (D). Accurate estimates of particle mass are thus essential to the accuracy of cloud products retrieved from remote sensing measurements [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Atmosphere 2020, 11, 756 2 of 16 water accretion, and melting/refreezing that lead to variability in ice-air mixtures [12]. Therefore, empirical power law m-D relationships taking the form m = aD b (1) have been widely used in numerical modeling and retrieval schemes. Various techniques and probes have been used to derive the a and b coefficients, and variations with temperature, particle habit, and cloud formation mechanism have been noted [13].…”
Section: Introductionmentioning
confidence: 99%